Model simulated freshwater transport along the Labrador current east of the Grand Banks of Newfoundland - Ma, Yongxing; Lu, Youyu; Hu, Xianmin; Gilbert, Denis; Socolofsky, Scott A.; Boufadel, Michel (Frontiers in Marine Science, 2022)
The freshwater transport (FWT) by the Labrador Current (LC) around the Grand Banks of Newfoundland (GBN) is diagnosed with the 26-year Global Ocean Physical Reanalysis 1/12-degree data (GLORYS12) during 1993 - 2018. The time-mean FWT of the LC above the 1027.25 kg/m3 isopycnal surface is 83.6mSv southward through the Flemish Pass. Among this 83.6mSv, 42% (35.2mSv) is exported into the interior of the North Atlantic along the whole pathway of the LC from the Flemish Pass to the Tail of the GBN, with 25.5mSv by the mean advection and 7.2mSv by the mesoscale eddy transport. The seasonal and inter-annual variations of the FWT in the east of the GBN are mainly caused by the variation of the horizontal velocity of the LC, and the variation of salinity makes a nontrivial contribution to the variation of the FWT to the north of 45N. Around the Tail of the GBN, the mesoscale eddies make significant contributions to the time-mean FWT and the seasonal and inter-annual variations of the FWT.